Respuesta :
Answer:
a) 0.58
b) 0.0464
Step-by-step explanation:
A= The person is sick
B= The give a positive result
P(A)=0.03
P(A')=1-P(A)=1-0.03=0.97
P(B|A)=0.9
P(B|A')=0.02
P(B)=P(B|A)P(A)+P(B|A')P(A')=0.9*0.03+0.02*0.97=0.0464
[tex]P(A|B)=\frac{P(B|A)P(A)}{P(B)}=\frac{0.9*0.03}{0.0464}=0.58[/tex]
You can sue the Bayes' theorem to find the needed probability.
The answers are (for A and B defined below)
a) P(A|B) = 0.5819 approximately
b) P(B) = 0.0464
What is Bayes' theorem?
Suppose that there are two events A and B.
Then suppose the conditional probability are:
P(A|B) = probability of occurrence of A given B has already occurred.
P(B|A) = probability of occurrence of B given A has already occurred.
Then, according to Bayes' theorem, we have:
[tex]\rm P(A|B) = \dfrac{P(B|A)P(A)}{P(B)}[/tex]
(assuming the P(B) is not 0)
Using that theorem to find the needed probabilities
Let the events be
A = Person has disease
B = Person is diagnosed positive for disease test.
Thus, from the given data, we have
P(A) = 0.03
P(A') = 1- P(A) = 0.97
P(B|A) = 0.9
P(B|A') = 0.02
Then we have:
a) Probability that disease is actually present if its given that person is diagnosed diseased = P(A|B)
Let A' be the event that person is not diseased. Then probability for B can be expressed as
P(B) = P(A')P(B|A') + P(A)P(B|A)
Thus,
[tex]\rm P(A|B) = \dfrac{P(B|A)P(A)}{P(B)} = \dfrac{P(B|A)P(A)}{P(B|A)P(A) + P(B|A')P(A')}[/tex][tex]\rm P(A|B) = \dfrac{0.9 \times 0.03}{0.9 \times 0.03 + 0.02 \times 0.97} \approx 0.5819[/tex]
b) Probability of positive test result =
P(B) = [tex]P(A')P(B|A') + P(A)P(B|A) = 0.9 \times 0.03 + 0.02 \times 0.97 = 0.0464[/tex]
P(B) = 0.0464
Thus,
a) P(A|B) = 0.5819 approximately
b) P(B) = 0.0464
Learn more about Bayes' theorem here:
https://brainly.com/question/16038936